PELUANG USAHA ATAP DAUN NIPAH BAGI MASYARAKAT DI KELURAHAN TIMBAU TENGGARONG KABUPATEN KUTAI KARTANEGARA PROVINSI KALIMANTAN TIMUR - Mastono Mastono; Jumani Jumani; Mohammad Taufan Tirkaamiana (Universitas 17 Agustus 1945 Samarinda, 2013)
Main utilization of Nipah tree is its leave as roofing material as the benefits that are generally known by the public. This benefits that provide added value should the presense of Nipah tree and it is not considered as a disturbing tree. Nipah tree beneficiary can be increased with the processed stems as animal feed of ducks and a variety of other benefits. By knowing the benefits then the palm leaves roof craftsman should also care for and manage the area as a source of raw material production. This study aimed to gain insight into the strengths, weaknesses, opportunities and threats as well as business strategies for sustainability in the roof af palm leaves. The data collection of this study using questionnaires and interviews with respondents craftsman palm leaf roof, with the number of respondents is 30 people. The data was analysed by using SWOT analysis. The results showed that business opportunity is still open and only there were few business competitors. Although the business opportunity is still open but the raw materials necessary to build that continues to exist and not be interruptedto facilitate the production of palm leaf roof. Roof of palm leaves businessmarketing opportunities still exist, but must have a strategy, although there is a chance the craftsman must remain priority order management and product quality still remains an alternative option after the metal roof price is quite expensive compared to the roof of palm leaves. Business opportunities palm leaves roof still promising but it still need efforts to exist and required product improvement, creativity, quality, and maintenance of raw material production area.